Kemampuan Bertanya Siswa dalam Kegiatan Diskusi Kelompok pada Materi Rasio Trigonometri - Faizah, Umi; Subanji, Subanji; Susiswo, Susiswo (Universitas PGRI Madiun, 2021)
Small group discussions (group work) are an important part of the learning process though students are rarely skilled at asking a question. The purpose of this study is to examine student interactions and questioning skills during group work. This research study uses a qualitative descriptive approach. The research subjects consist of eight students who were divided heterogeneously into two groups, with four members for each group. The research instrument consists of the researcher herself, a task in the form of a trigonometric ratio group worksheet, and three video cameras to observe discussion activities. One camera was focused on all class activities and two cameras were pointing at each group being observed. All conversation transcripts during the discussion are deciphered, coded, and then analyzed qualitatively. The results of this study show the interaction of conveying opinion/rebuttals, asking questions, and providing answers, with the percentage of giving opinions/ objections were more dominant than other interactions. The ability to ask questions was obtained by 50% of the students having the medium questioning ability and 50% having the low questioning ability, with the level of questions asked at the LOTS level, namely C1 and C3 levels. None of the students had high questioning skills. Of the two groups observed, group A was more active in interacting both in terms of exchanging opinions/rebuttals, asking questions, and providing answers. Suggestions for further research need to be carried out an in-depth analysis of discussion activities both in terms of asking questions or providing feedback to see the emergence of collaborative reasoning.